PROSPEK TEMPAT PELELANGAN IKAN (TPI) DI KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Mulia, Windi Tri; Chandra, Deded (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
A fish auction place is a special facility for auctioning fish caught by fishermen with the aim of creating an efficient and transparent system in sales. The auction process is carried out with manual mechanisms or digital technology to determine prices fairly. The importance of fish auctions to stabilize prices, increase fishermen's income, and support the conservation of fish resources. This study aims to determine how the opportunity to develop a Fish Auction Place (TPI) in Koto XI Tarusan District, South Pesisir Regency using qualitative approaches and descriptive methods. Research data was collected through observation, interviews, and documentation at TPI Carocok Anau and Ampang Pulai. The main informants consisted of fishermen and fishermen leaders who played a role in TPI's opportunities in the region. The results showed that TPI in Koto XI Tarusan District has great potential to support the local economy. However, inadequate infrastructure and access barriers are obstacles. The government needs to pay attention to the development of TPI, including infrastructure improvements and accessibility for fishermen. Transactions at TPI are large-scale by involving agents as intermediaries. The existence of fish demolition areas such as Batu Kalang and Muara is important in supporting the fishermen's economy. Cooperation between the government and fishermen is needed to improve TPI's prospects as a center for marketing local fish and support sustainable regional economic growth.